2020
DOI: 10.1073/pnas.1917423117
|View full text |Cite
|
Sign up to set email alerts
|

Chronic mild stress alters synaptic plasticity in the nucleus accumbens through GSK3β-dependent modulation of Kv4.2 channels

Abstract: Although major depressive disorder (MDD) is highly prevalent, its pathophysiology is poorly understood. Recent evidence suggests that glycogen-synthase kinase 3β (GSK3β) plays a key role in memory formation, yet its role in mood regulation remains controversial. Here, we investigated whether GSK3β activity in the nucleus accumbens (NAc) is associated with depression-like behaviors and synaptic plasticity. We performed whole-cell patch-clamp recordings of medium spiny neurons (MSNs) in the NAc and determined th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
29
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 87 publications
6
29
0
2
Order By: Relevance
“…Consistent with the hypothesis of beta-catenin having therapeutic effects, overactive GSK-3b is associated with depressive symptoms [98]. Also, GSK-3b mediates maladaptive NAc plasticity [99], and knockdown prevents depressive symptoms. GSK-3b is also inhibited lithium, and ketamine, which is necessary for its antidepressant effects [18].…”
Section: Set Intersectionsupporting
confidence: 64%
“…Consistent with the hypothesis of beta-catenin having therapeutic effects, overactive GSK-3b is associated with depressive symptoms [98]. Also, GSK-3b mediates maladaptive NAc plasticity [99], and knockdown prevents depressive symptoms. GSK-3b is also inhibited lithium, and ketamine, which is necessary for its antidepressant effects [18].…”
Section: Set Intersectionsupporting
confidence: 64%
“…In association with the chronic stress-induced changes in the excitability of MSNs, several studies have reported changes in dendritic spine structure and density, which involve various neurotrophic factors, cell adhesion molecules, and kinases [104][105][106][107] . However, these findings are contradictory in terms of the correlation between these structural changes in spines and depressive/resilient behavior, which thus remains to be elucidated (Table 2).…”
Section: Chronic Stress-induced Plasticity Changes In Msns In the Nacmentioning
confidence: 99%
“…Synaptic plasticity and cognition are affected by stress (Russo and Nestler, 2013, Dwivedi and Pandey, 2000, Aceto et al, 2020). While acute stress can improve cognitive performance, exposure to persistent stress causes cognitive impairment (Yuen et al, 2012, Bellani et al, 2006).…”
Section: Resultsmentioning
confidence: 99%